Pilihan Rasional Orang Tua Menitipkan Anak Di Baby Daycare - Reski, Putri; Marnelly, T. Romi; Risdayati, Risdayati; Resdati, Resdati (UIR PRESS, 2022)
Sociologically, the family has important role in the parenting process. This role is carried out by parents, especially mothers. Currently, there is a part of mothers not only work in the domestic sector but also in the public sector. This means that this parenting role needs to be taken by other socialization agents so that parents can still work. So this study aims to determine the rational choice of parents to leave their children in the TPA and to find out the process of parents choosing Siti Walidah Baby Daycare as a substitute daycare place. This study uses descriptive qualitative research methods. The study included daycare manager and 5 informants from the parents. In determining the subjects in this study, the authors used a purposive sampling technique with the criteria of parents or guardians choosing the full daycare program, entrusting more than one child, and having children aged 0 to 5 years. According to the study's findings, all research subjects, as parents, have the same motivation for leaving their children in daycare; whereas they previously began with their situation and their partners, who work 8 hours a day in office operations and no one takes care of children at home, they are now looking for other alternatives to fill the role. child care, compare one day care center with another, and also consider all aspects to decide the choice they take. In the end, they decide to go with Siti Walidah Babysitting.